Rancang Bangun Aplikasi Sistem Pakar Diagnosa Penyakit Stunting Berbasis Web Menggunakan Metode Certainty Factor - Dini Destiani Siti Fatimah; Yosep Septiana; Gilang Ramadhan; Yeni Pariyatin (Institut Teknologi Garut, 2022)
Stunting is a disease of child growth and development which is characterized by low body height and with increasing age the body still does not develop properly according to its age and lasts a long time. Stunting can be triggered by several factors including infection or malnutrition in pregnant women, malnutrition in infancy, and poor stimulation from the environment. Along with the development of technology in the world of health such as expert system applications that can function to help someone to diagnose a disease. An expert system for diagnosing stunting can help the community find out whether their child is stunted or not, so stunting can be followed up quickly. Therefore the purpose of this research is to create an expert system that can detect stunting. The method used in this expert system is the certainty factor method by utilizing data on stunting symptoms. The web-based application is designed using the ESDLC (Expert System Development Life Cycle) expert system application development method and the blackbox testing method. The result of this research is the application of a web-based expert system for diagnosing stunting. This research is expected to be a tool that makes it easier for parents who have toddlers to diagnose stunting.